2017
DOI: 10.1016/j.aap.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Cross-classified multilevel models for severity of commercial motor vehicle crashes considering heterogeneity among companies and regions

Abstract: This study analyzes 86,622 commercial motor vehicle (CMV) crashes (large truck, bus and taxi crashes) in South Korea from 2010 to 2014. The analysis recognizes the hierarchical structure of the factors affecting CMV crashes by examining eight factors related to individual crashes and six additional upper level factors organized in two non-nested groups (company level and regional level factors). The study considers four different crash severities (fatal, major, minor, and no injury). The company level factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 31 publications
1
25
0
3
Order By: Relevance
“…In the event of a crash, factors related to intersections and exclusive bus lanes were associated with more severe crashes. In the case of exclusive bus lanes, the excessive speed of buses with a separate travel priority may increase the injury severity of pedestrians in crashes, which was supported by the findings of previous studies [13,26]. However, the effect of intersections has proven to be controversial.…”
Section: Crash-level Factorsmentioning
confidence: 60%
See 3 more Smart Citations
“…In the event of a crash, factors related to intersections and exclusive bus lanes were associated with more severe crashes. In the case of exclusive bus lanes, the excessive speed of buses with a separate travel priority may increase the injury severity of pedestrians in crashes, which was supported by the findings of previous studies [13,26]. However, the effect of intersections has proven to be controversial.…”
Section: Crash-level Factorsmentioning
confidence: 60%
“…There is growing interest in the use of multi-level models to analyze hierarchically structured traffic crash data, and these models are often referred to as hierarchical models [1,[7][8][9][10][11][12][13][14][15]. Two research studies have summarized the use of multi-level analysis of traffic crash data and suggested further studies [14,15].…”
Section: Multi-level Models In Traffic Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…We thus distinguish three different levels, the individual offender level and two community levels. Cross-classified multilevel models, which have already been widely used in other domains [51,52], have not yet been used in journey-to-crime studies, but they are well-suited to analyze data of this structure [53]. In total, we had 3763 crime trips nested in 1117 home communities and 1382 target communities.…”
Section: Methodsmentioning
confidence: 99%